2000
DOI: 10.1016/s0741-5214(00)70078-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of segmental spinal cord perfusion on intrathecal oxygen tension during experimental thoracic aortic crossclamping

Abstract: In this experimental model of aortic crossclamping, continuous CSF oxygen tension monitoring allows rapid detection of alterations in spinal cord circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This method was validated with epidural laser Doppler flowmetry. 1,2 The percutaneous use of the Paratrend catheter was also reported in a patient undergoing thoracoabdominal aortic surgery. 3 Recently, Ishizaki and coworkers 16 have reported the use of a rigid mass spectrometer probe for CSF PO 2 measurements during experimental aortic occlusion for identification of spinal cord feeding arteries.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This method was validated with epidural laser Doppler flowmetry. 1,2 The percutaneous use of the Paratrend catheter was also reported in a patient undergoing thoracoabdominal aortic surgery. 3 Recently, Ishizaki and coworkers 16 have reported the use of a rigid mass spectrometer probe for CSF PO 2 measurements during experimental aortic occlusion for identification of spinal cord feeding arteries.…”
Section: Discussionmentioning
confidence: 97%
“…The present study was designed to evaluate the correlation between CSF parameters derived with the Paratrend catheter and structural changes in the spinal cord in a previously reported aortic occlusion model in pigs. 1 Other studies on spinal cord ischemia have demonstrated a satisfactory correlation between histopathologic spinal cord changes and functional outcome evaluated by use of the Tarlov criteria. [17][18][19][20][21][22] Yamamoto and coworkers 21 observed no morphologic ischemic spinal cord degeneration if normal hind leg function was present.…”
Section: Discussionmentioning
confidence: 99%